Involvement of the NADPH oxidase 2 pathway in renal oxidative stress in Aqp11-/- mice - Yuya Hoshino; Hiroko Sonoda; Ryuji Nishimura; Kazuya Mori; Kenichi Ishibashi; Masahiro Ikeda (Biochemistry and Biophysics Reports, 2019)
Aquaporin-11 (AQP11) is an intracellular AQP. Several studies with Aqp11-/- mice have shown that AQP11 has a role in normal development of the kidney after birth. Our previous studies have suggested that alteration of oxygen homeostasis may be involved in the kidney injury caused by AQP11 deficiency, although the underlying mechanism is largely unknown. To clarify this issue, we examined genes that are related to oxygen homeostasis in Aqp11-/- mice. Among 62 genes that are involved in oxygen homeostasis, 35 were upregulated by more than 2-fold in Aqp11-/- mice in comparison with wild-type mice. Pathway analysis using these genes extracted the pathway responsible for production of reactive oxygen species in macrophages. As expression of the genes involved in the NADPH oxidase 2 (NOX2) complex was dramatically increased by more than 14-fold, we further analyzed NOX2 at the protein level. Immunoblotting analysis demonstrated a dramatic increase of NOX2 protein in the kidney of Aqp11-/- mice, and immunohistochemistry showed that NOX2 protein and a marker protein for macrophages were increased in the renal interstitium. These results indicate that NOX2-induced oxidative stress accompanied by macrophage infiltration plays an important role in alteration of oxygen homeostasis in Aqp11-/- mice. Keywords: Aquaporin-11, Polycystic kidney disease, Oxidative stress, Hypoxia, Renal failure, Pathway analysis, NOX2